THE CONTRIBUTION OF DA'WAH IN SHAPING LEGAL BEHAVIOR OF URBAN COMMUNITIES MATARAM CITY - Syaoki, Muhammad; Muhammad Fikri (Universitas Islam Negeri (UIN) Mataram, 2024)
Da'wah activities should be able to bring about changes in the body of the ummah, including forming legal behavior which includes legal compliance, legal awareness, understanding of rights and obligations as well as ethics and morals. The more often a person participates in da'wah activities, the better his legal behavior should be. By using a qualitative method, this research tries to reveal the contribution of da'wah in shaping the legal behavior of Muslim communities in the city of Mataram. The results of this study show the contribution of da'wah in the formation of legal behavior of Muslim communities in the city of Mataram. The contribution is influenced by four factors, namely first, the attachement between the community (mad'u) and Tuan Guru/Ustadz (da'i). Second, the commitment of the community (mad'u) to follow what is conveyed by da'i in the da'wah activities they participate in. Third, involvement (involvment) refers to the intensity of the community in da'wah activities. Fourth, belief refers to the internalization of the values of religious teachings absorbed in the da'wah activities they participate in.